What did they sing at Cashel in 1172?: Winchester, Sarum and Romano-Frankish Chant in Ireland - Lawrence, Frank (Journal of the Society for Musicology in Ireland, 2008)
The Second Council of Cashel in 1172, at which many of the Irish bishops swore fealty to King Henry II, is usually credited with the introduction of English and in particular, Sarum liturgical and musical usage to Ireland. This article examines the historical, musical and liturgical context of the Cashel gathering, challenging traditional interpretations of this event. It demonstrates that the Council could not have decreed the introduction of Sarum usage to Ireland and that Cashel was not a watershed heralding the demise of the ‘Celtic rite’. Using the earliest complete surviving Irish plainchant source (GB-Ob Rawl. C. 892), it suggests that the twelfth-century Irish Church was already open to a wide range of musical and liturgical influences from England (principally Winchester) and continental Europe. The musical and liturgical evidence from notated and un-notated twelfth-century sources obliges us to re-formulate our ideas about this important time of development and transition in Irish musical and cultural life.